Leveraging Mutual Coupling in Antenna-Amplifier Systems for Increased Reconfigurability - Jaanus Kalde; Veli-Pekka Kutinlahti; Anu Lehtovuori; Alvo Aabloo; Ville Viikari (IEEE Journal of Microwaves)
Traditional antenna array design aims at minimising the mutual coupling between the elements. When elements are fully isolated, the active impedance seen by the amplifiers does not depend on the beam steering angle. However, at the same time, the mutual coupling can not be exploited in re-configuring the operation of the antenna-amplifier system. In this paper, we show experimentally that increased mutual coupling between array elements can broaden the operation band of the system without any sacrifice in the efficiency or transmitted power. This severely challenges the traditional design paradigm and suggests that amplifiers and antennas should be co-designed.